Impact of 2016 ASE/EACVI recommendations on evaluation of left ventricular diastolic function and clinical outcomes in patients with diabetes and hypertension without prior adverse cardiac events. (25th November 2020) - Foo, D; Lam, K.H; Igo, M; Bujang, M.A; Ku, M.Y; King, T.L; Yeo, L.S; Ahip, S.S; Sahiran, M.F; Mustapha, M; Michael, J; Abdullah, A; et al.
Abstract: Background: Left ventricular diastolic dysfunction (LVDD) has been shown to be more prevalent in patients with diabetes, and once progress to overt heart failure, carry worse clinical outcomes, compared to those without diabetes. The complexity of previous 2009 ASE/EACVI algorithms makes diastolic function (DF) assessment challenging. Hence, prognostic value of LVDD estimates in clinical setting is not well-established. Objective: To evaluate the impact of 2016 recommendations in estimates of LVDD and predicting cardiovascular outcomes in patients with diabetes and hypertension. Materials and methods: A total of 111 patients with diabetes and hypertension who attended diabetic clinic follow-up at the primary healthcare settings were enrolled. All patients were clinically NYHA Class I, had no prior adverse cardiac events, and had preserved left ventricular (LV) ejection fraction on echocardiography at screening. Echocardiography was performed to obtain parameters of LV dimensions, LV volumes and LVDD. Both 2009 and 2016 algorithms were applied in DF assessment. All patients follow-up at 1 year to assess clinical outcomes. Results: There were 65 (58.6%) female patients. Mean age was 59.86 (7.45); mean duration of diabetes was 10.5 (5.41). 55 (50.5%) patients had LV hypertrophy on echocardiography. Prevalence of LVDD (14.4% vs 55.0%) and elevated LV filling pressure (9.0% vs 26.1%) were lower with 2016 compared with 2009 recommendations. Prevalence of indeterminate DF was 18.0% and 12.6% according to 2016 and 2009 recommendations respectively. Concordance between 2016 and 2009 recommendations was fair (k=0.29, p<0.001), with a reclassification rate of 45.9%. None out of 45 patients who were diagnosed with indeterminate and normal DF according to 2016 and LVDD with 2009 algorithms developed MACE at 1 year. Out of 12 patients diagnosed with LVDD based on both 2016 and 2009 recommendations, 4 patients developed MACE at 1 year. 2016 recommendations showed better accuracy (sensitivity=80.0%; specificity=88.68%) than 2009 recommendations (sensitivity=80.0%; specificity= 45.28%) in predicting MACE at 1 year. Conclusions: The application of 2016 recommendations results in lower prevalence of LVDD. The 2016 criteria detect more advanced cases and predict 1 year cardiovascular outcomes better. Further studies are warranted to investigate the prognostic impact of this criteria. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institute of Health (NIH), Ministry of Health Malaysia